Keterampilan Pengolahan Mie Sehat dari Sayur Sawi untuk Meningkatkan Gizi dan Imunitas Tubuh di Desa Sei Asam Kelurahan Sei Pasa Kabupaten Kapuas Kalimantan Tengah - Adelgrit Trisia; Indria Augustina; Dian Mutia (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2018)
Noodle is a popular food product and widely consumed by the people in Indonesia. The world of commerce knows noodles in a variety of products Because the main ingredients are wheat flour, tapioca flour or rice flour, then the greatest nutritional content in noodles and processed products is carbohydrates. Foods consumed with unbalanced nutritional content, which are high in fat/oil, high carbohydrate, high salt, and low in fiber. The impact that occurs with food with unbalanced nutrition, for the long term is the emergence of degenerative diseases such as diabetes, cardiovascular diseases such as heart and hypertension, and cancer and others. The main objective is to increase knowledge and understanding of the villagers of Sei Asem regarding the processing of healthy noodles based on vegetables. Specific Objectives To help improve the knowledge of villagers to process healthy noodles made from vegetables. Attempts to raise awareness of the villagers about the importance of processing food based on the healthy life of the household. Attempts to improve the health status of the community in the village of Sei Asam Method of Implementation of Community Partnership Program activities by way of counseling, training and mentoring. The results obtained from this activity is the increasing knowledge of the villagers about the benefits of Sawi vegetable, processing of sawi vegetables into noodles and one of the efforts to increase the consumption of balanced nutrition that can increase immunity.